Participatory Design in Interior Architecture: A Proposal for the Factors of Adaptive Reuse with User Participation - Barani, Mahshid; Dastranj, Farnaz (Street Art & Urban Creativity, 2023)
Nowadays, we are facing a huge number of old buildings which are abandoned or become demolished due to a change in their function or loss of resistance. Meanwhile, adaptive reuse offers sustainable strategies in which by spending less energy and money, not only is it possible to use the capacity of the building, but also, in heritage cases, it increases attention to the values of the building and has cultural and social effects. In addition, the participatory design approach can assist the designer in improving efficiency by engaging the user in different stages of the design process. In this paper, the specified process in adaptive reuse, and participatory design in the building environment are studied by referring to the library sources. We identified how the user engages in design planning with the descriptive-analytical method